2016
DOI: 10.1007/s11414-016-9543-6
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of the National Health Care Surveys to Examine Behavioral Health Services Associated with Polycystic Ovary Syndrome

Abstract: The National Institutes of Health, Office of Disease Prevention, has described polycystic ovary syndrome (PCOS) as a major public health problem for women in the USA. This study examines the suitability of the National Health Care Surveys, collected by the Centers for Disease Control and Prevention, to understand patient demographics and behavioral health services associated with PCOS-related medical visits. Data were from the 2005–2010 National Ambulatory Medical Care Survey and National Hospital Ambulatory M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Furthermore, in studies investigating comorbidities of PCOS, when the diagnosis was made based on ICD codes, challenges were encountered. For example, in a study [ 29 ] which examined data from the National Health Care Surveys to understand patient demographics and behavioral health services associated with ICD coded PCOS-related medical visits, the study found that data on mental health and health education did not meet the necessary criteria for reliable national estimates. Unfortunately, it is unlikely that recent attempts to improve the international federation of gynecology and obstetrics (FIGO) classification of ovulatory disorders [ 30 ] will address these challenges as even though the new classification now includes ovulatory disorders categorized into four groups, with a new stand-alone category for PCOS, in the development process using a Delphi approach, no consensus was reached on the question of using the Rotterdam criteria for the diagnosis of PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in studies investigating comorbidities of PCOS, when the diagnosis was made based on ICD codes, challenges were encountered. For example, in a study [ 29 ] which examined data from the National Health Care Surveys to understand patient demographics and behavioral health services associated with ICD coded PCOS-related medical visits, the study found that data on mental health and health education did not meet the necessary criteria for reliable national estimates. Unfortunately, it is unlikely that recent attempts to improve the international federation of gynecology and obstetrics (FIGO) classification of ovulatory disorders [ 30 ] will address these challenges as even though the new classification now includes ovulatory disorders categorized into four groups, with a new stand-alone category for PCOS, in the development process using a Delphi approach, no consensus was reached on the question of using the Rotterdam criteria for the diagnosis of PCOS.…”
Section: Discussionmentioning
confidence: 99%
“…With the further development of the disease, severe menstrual disorders, loss of sexual desire, and even infertility and abortion occur. It is mainly manifested by excessive LH secretion, and the disorder of gonadotropin level secreted by the pituitary gland is very likely to lead to follicular dysplasia and hyperandrogenemia [ 26 ]. Generally, patients' condition will improve after Western medicine treatment, but some patients have poor compliance, tolerance, and side effects, and long-term alternative treatment also increases the risk of angina, myocardial infarction, osteoporosis, and fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that so many women are affected by PCOS, the NIH has failed to grasp the issue of the psychological needs of these women [31]. Thus it is little wonder that women with PCOS suffer from long-term mental health issues [32].…”
Section: Consequences Of the Hypotheses And Discussionmentioning
confidence: 99%